Defluoridation of groundwater from Siloam Village, Limpopo Province, South Africa, using vermiculite modified with hexadecyltrimethylammonium. Issue 1 (1st January 2020) - Ologundudu, Tayo O.; Durowoju, Olatunde S.; Odiyo, John O.; Ekosse, Georges-Ivo E.
Abstract: South Africa is a water-scarce nation, and this has resulted to the use of groundwater as one of the alternative sources. Owing to the low socio-economic status of some communities in rural areas, where modern water purification equipment is not available, groundwater is consumed without prior treatment. Siloam Village, Limpopo Province, is one of such communities; however, the presence of excess fluoride in groundwater has led to the occurrence of fluorosis, which constitutes a health concern. Vermiculite which is a clay mineral is highly available in Limpopo Province and has not been exploited for defluoridation; thus, this study was aimed at the defluoridation of groundwater in Siloam Village using vermiculite modified with hexadecyltrimethylammonium, a cationic surfactant with antimicrobial properties. The clay mineral was activated with NaCl and subsequently modified by agitating with the surfactant in a 5%w/v solution. The pzc of the modified vermiculite was deduced to be 6.4 while that of the control vermiculite was 9.7. Using groundwater from sampling points GW 1 and GW 2 for defluoridation studies, the results show 22.27% and 20.72% removal while a maximum of 49.4% was obtained from a 5 mg/L laboratory simulated fluoride solution. The effect of competing anions especially CO3 2-, as well as the low electro-positivity on the surface of the modified vermiculite reduced the fluoride sorption potential of the adsorbent. Thus, the use of vermiculite modified with hexadecyltrimethylammonium is not a very suitable option for solving the problem of fluorosis in rural environments.